In vitro evaluation of biological activities of citrus leaf extracts - Muhammad Adnan; Atika Umer; Imtiaz Ahmad; Khizar Hayat; Samina N. Shakeel (Universiti Kebangsaan Malaysia, 2014)
Leaves extracts of three different citrus species namely Citrus sinensis (Malta), Citrus paradisi (Grape fruit) and Citrus jambhiri (Khatti) were evaluated for their antioxidant, cytotoxic, antitumor, antimicrobial activities and finally the mineral contents were determined. Four types of extraction solvents (100, 80 and 50% methanol and distilled water heated at 50oC) were used for extraction of antioxidant compounds. Extracts yield increased with the elevated levels of aqueous component of organic solvent and our data showed the highest yield in aqueous extracts. All extraction regimes showed in vitro antioxidant activity. Citrus paradisi showed the highest total flavonoid content (TFC), total phenolic content (TPC), reducing power and 1,1-Diphenyl-2- picrylhydrazil free radical scavenging activity in all combinations of solvents followed by Citrus sinensis and Citrus jambhiri. Antioxidant activity was also increased with higher aqueous component of organic solvents in each case. While Citrus sinensis (in 100% methanolic solvent) and Citrus paradisi (in 50% methanolic extract) showed significant cytotoxicity (LD50 values <1000). Antitumor activity was observed in all extracts, however Citrus sinensis and Citrus paradisi (in 50% aqueous methanolic) extracts had the highest antitumor activity from the selected citrus species whereas no antimicrobial activity was observed at higher concentrations (4000 μgmL-1) against specified strains. We found high calcium contents in all three citrus species tested by atomic absorption method. The results showed that the leaves of selected Citrus species possess significant antioxidant, antitumor and cytotoxic activities. Citrus leaves extracts can be potentially helpful in antioxidant protection in food as well as in human body against lipid peroxidation and free radicals damage. It can further be evaluated after in vivo studies using animal models or identifications of high throughput methods for enhanced biological activities.